Reactions to Dream Content: Continuity and Non-continuity - Kahn, David (Frontiers in Psychology, 2019)
Although dream content may at times be quite outlandish or illogical, the dreamer’s emotional reactions to these events are not outlandish or illogical. Our study shows that the dreamer’s emotional reaction to people and events are similar to what they would have been in wake life. There is continuity between the emotional reactions of the dream and wake-self, even though situations may arise that are not likely or possible in wake life. For example, a dream may include people and places that span different times that are weaved together as if they were occurring at the moment. Further, the behavior of the dream-self is often different than that of the wake-self. When this happens, there is a non-continuity between the behavior of the dream and wake-self. Thus, there is both continuity and non-continuity between the dream and wake-self: Continuity in emotional reactions and non-continuity in the kinds of situations and behaviors that occur while dreaming. In the Kahn and Hobson, 2005a study, 58.7% of participants reported that their thinking within the context of the dream was similar to what it would have been had they been awake. About 55.1% of participants also reported that their thinking about the context of the dream was different than it would have been had they been awake. This difference affords the dream-self with novel experiences but that still elicit emotional reactions that are similar to how its wake-self would react. In essentially, every case when a comment was given to the question on thinking in the Kahn and Hobson, 2005a study, participants reported about how they emotionally reacted within the context of the dream and how they emotionally reacted about the content of the dream in comparison to how they would have reacted if awake.